Stimuli-responsive hydrogel patterns for smart microfluidics and microarrays - Kang, Do Hyun; Kim, Sang Moon; Lee, Byungjun; Yoon, Hyunsik; Suh, Kahp-Yang (Analyst (London), 2013)
In this review, we highlight the properties, functions and applications of stimuli-responsive hydrogel patterns in bioanalytical applications. Stimuli-responsive hydrogel patterns can be realized by well-established micro- and nanofabrication technologies such as photolithography and micromolding, and are currently adopted as active components for manipulation of flow and biosamples in microchannel and microarray systems. We overview the properties of stimuli-responsive hydrogel materials and their fabrication methods along with some representative examples in microfluidics and microarrays.